The management of dynamic epistemic relationships regarding second language knowledge in second language education: Epistemic discrepancies and epistemic (im)balance. Issue 2 (3rd May 2016) - Rusk, Fredrik; Pörn, Michaela; Sahlström, Fritjof
Abstract: Using the first language (L1) to solve problems in understanding the second language (L2) may be beneficial for L2 learning. However, the overuse of L1 may deprive L2 learners of exposure to the L2. It appears that the question is not whether to use L1 or L2; it is when and how each language can be used to support L2 learning. This study focuses on situations in L2 education in which L1 is not used in an attempt to solve the L2 learner's problems of understanding the L2 and the current assignment. The aim is to investigate what role participants' management of each other's L2 knowledge plays in maintaining intersubjectivity and doing L2 learning in these situations. The results show that participants may act on diverse L2 knowledge and diverse possible understandings regarding the assignments and that the use of L2 risks expanding these epistemic discrepancies. Using L2 also appears to restrict doing L2 learning on conceptual knowledge, for example, word-meanings. The participants agree on a minimally required epistemic balance as a way to move on. The use of L1 as needed in these situations, as a resource for meaning-making, may be beneficial for doing L2 learning.